1992
DOI: 10.1126/science.1631558
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Hemophilia B Leyden: An Androgen-Responsive Element in the Factor IX Promoter

Abstract: One form of the inherited, X-linked, bleeding disorder, hemophilia B, resolves after puberty. Mutations at -20 and -26 in the clotting factor IX promoter impair transcription by disrupting the binding site for the liver-enriched transcription factor LF-A1/HNF4. The -26 but not the -20 mutation also disrupts an androgen-responsive element, which overlaps the LF-A1/HNF4 site. This explains the improvement seen in patients with the -20 mutation and the failure of the -26 patient to recover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
3
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 20 publications
13
139
3
1
Order By: Relevance
“…(32,33). In addition to substitutions affecting Spl binding, naturally occurring promoter mutations that link deficient transcription factor binding to human disease have been described for a C/EBP site (6), for an LF-A1/HNF4 site and an ARE in the factor IX promoter (34), and for an ATF site in the retinoblastoma gene (5 …”
Section: Discussionmentioning
confidence: 99%
“…(32,33). In addition to substitutions affecting Spl binding, naturally occurring promoter mutations that link deficient transcription factor binding to human disease have been described for a C/EBP site (6), for an LF-A1/HNF4 site and an ARE in the factor IX promoter (34), and for an ATF site in the retinoblastoma gene (5 …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, experimental searches for AREs have focused on short genomic segments just upstream of the transcription start sites of individual genes (Loreni et al 1988;Crossley et al 1992;Murtha et al 1993;Rennie et al 1993;Cleutjens et al 1996); computational approaches have used predefined ARBS motifs to query these same regions, albeit with only modest success Steketee et al 2004;Magee et al 2006). …”
mentioning
confidence: 99%
“…5 This may be the result of the initiation of a diurnal metabolic cycle at puberty 11 or with changes in sex hormone regulation. 14 The ability of site 5 activity to complement mutations in any of three proximal promoter binding elements suggests that site 5 plays a dominant role in promoter regulation. By introducing a site 5 multimer into the promoter we would expect these constructs to function optimally in children, maintain their tissue specificity, and operate at near physiological levels.…”
Section: Figure 6 Effect Of C/ebp␣ Co-transfection On Expression a Cmentioning
confidence: 99%
“…13 It has been suggested that recovery is correlated with the induction of sex steroid hormones at puberty and their activation of an androgen receptor site in the proximal promoter. 14 Alternatively, we have demonstrated that a site approximately 200 nucleotides upstream of the transcription start site (site 5), plays a key role in the recovery of transcriptional activity during puberty. 11 This element was seen to be a prime regulator of the Factor IX promoter, with point mutations in this element resulting in a dramatic decrease in promoter activity.…”
Section: Introductionmentioning
confidence: 99%